Between Two Worlds: The Impact of Sociocultural Acculturation on the Psychological Well-being - Chen, Haojun; Zhang, Wenzhuo; Lai, Chengye; Jiang, Ting (International Journal of Asian Education, 2025)
The sociocultural adaptation of Mainland Chinese students in Hong Kong presents unique challenges that significantly impact their psychological well-being. While Hong Kong shares cultural similarities with Mainland China, historical, political, and linguistic differences create distinct adaptation barriers for non-local students. This study examines the relationship between sociocultural adaptation difficulties and psychological distress among Mainland Chinese students, emphasizing the impact on anxiety, social impairments, and depression. Using a quantitative approach, data were collected from 245 students through a structured survey incorporating the Sociocultural Adaptation Scale and the General Health Questionnaire-28 (GHQ-28). Pearson correlation analysis revealed a strong positive association (r= 0.79, p < 0.05) between adaptation difficulties and psychological distress. Further analysis indicated that social impairments and anxiety/insomnia were the most affected mental health dimensions, while longer duration of stay in Hong Kong was linked to improved adaptation and reduced psychological distress. These findings highlight the need for targeted interventions to support Mainland Chinese students in overcoming adaptation stress. Universities should enhance peer mentorship programs, language support services, and intercultural initiatives to foster social inclusion and reduce psychological distress. Future research should explore qualitative perspectives to gain deeper insights into students' lived experiences and the long-term effects of acculturation stress. By addressing these challenges, higher education institutions can create a more supportive and inclusive environment that enhances both academic success and student well-being.